AKTIVITAS ANTIINFLAMASI EKSTRAK METANOLIK BUAH MANGGA KASTURI (Mangifera casturi) MELALUI PENGHAMBATAN MIGRASI LEUKOSIT PADA MENCIT YANG DIINDUKSI THIOGLIKOLAT - Nanang Fakhrudin; Peni Susilowati Putri; Sutomo Sutomo; Subagus Wahyuono (Majalah Obat Tradisional, 2013)
Kasturi (Mangifera casturi) is a plant originally from Kalimantan, mainly in South Kalimantan. Although there is no report regarding the usage of the fruit in traditional healings, current research demonstrate that methanolic extract of Mangifera casturi fruit demonstrated high antioxidant activity. As oxidant plays crucial role in inflammatory related diseases, we investigate the antiinflammatory effect of Mangifera casturi fruit methanolic extract. To assess the antiinflammatory activity, we used thioglycollate-induced leukocyte migration in mice.  Male balb/c mice were pretreated (i.p) with Mangifera casturi fruit methanolic extract followed by thioglikolat (i.p) to induce leukocyte migration. After 4,5 hours, the mice were sacrificed and the number of leukocytes were counted using hemocytometer under light microscope.   Our experiment indicates that Mangifera casturi fruit methanolic extract significantly exhibited antiinflammatory activity by inhibiting the migration of leukocytes induced by thioglycollate. However, the activity of the extracts was lower than the positive control, indomethacin. Further purification was required to obtain the active compound with the activity comparable to indomethacin. Thin layer chromatography (TLC) analysis demonstrates that the methanolic extract of Mangifera casturi fruit contains terpenoid and phenolic compounds.